Effects of Epithelial to Mesenchymal Transition on T Cell Targeting of Melanoma Cells - Woods, Katherine; Pasam, Anupama; Jayachandran, Aparna; Andrews, Miles C.; Cebon, Jonathan (Frontiers in Oncology, 2014)
Melanoma cells can switch phenotype in a manner similar to epithelial to mesenchymal transition(EMT). In this perspective article, we address the effects of such phenotype switching on T cell targeting of tumour cells. During the EMT-like switch in phenotype, a concomitant change in expression of multiple tumour antigens occurs. Melanoma cells undergoing EMT escape from killing by T cells specific for antigens whose expression is downregulated by this process. We discuss melanoma antigens whose expression is influenced by EMT. We assess the effect of changes in the expressed tumour antigen repertoire on T cell mediated tumour recognition and killing. In addition to escape from T cell immunity via changes in antigen expression, mesenchymal-like melanoma cells are generally more resistant to classical chemotherapy and radiotherapy. However, we demonstrate that when targeting antigens whose expression is unaltered during EMT, the capacity of T cells to kill melanoma cell lines in vitro is not influenced by their phenotype. When considering immune therapies such as cancer vaccination, these data suggest escape from T cell killing due to phenotype switching in melanoma could potentially be avoided by careful selection of target antigen